Data Perception and Information Disorder in the Italian Context During the Pandemic - Giovanni Ciofalo; Lorenzo Ugolini; Fabio Ciammella (VIEW Journal of European Television History and Culture)
This paper aims to investigate how Italian audiences received and perceived data-driven television news during the Covid-19 pandemic. During this time, the logic and practices of creating and consuming television journalism were disrupted by the pandemic emergency. The paper presents the results of research carried out as part of a wider project titled “The Social Effects of Fake News” which was conducted from 2018 to 2022 within the CoRiS department of Sapienza University of Rome. The research project was reshaped in 2020, to understand the effects of what has been called “information disorder” in the areas of health, medicine, and science at a time when, together with the pandemic, an “infodemic” also emerged.1 We use Wardle and Derakhshan’s notion of “information disorder” as presented in their Council of Europe report.2